MAKING WEBSITE FOR PROMOTIONS USED MOTOR SALES USING PHP MySQL & Macromedia Dreamweaver 8.0. - Fauzi Rachman; Sutarno Sutarno (Jurnal Sistem Informasi, 2009)
In the development of rapid information technology so that more current  easy for every person in getting information. Information can be obtained  in various respects, especially in a world growing used bike sales  more rapidly. Therefore, a former motorcycle sales service named  OzyMotor offers convenience for you in the information used bike sales.